Amanda Bean's amazing dream : a mathematical story - Neuschwander, Cindy; Burns, Marilyn, 1941-; Woodruff, Liza (New York : Scholastic Press, 1998)
Amanda loves to count everything, but not until she has an amazing dream does she finally realize that being able to multiply will help her count things faster.
"A Marilyn Burns brainy day book.".
Book Links (A.L.A.).
Elem. School Library Collection.
School Library Journal.
2.5
K-3
Keywords: Arithmetic -- Fiction; Dreams -- Fiction; Multiplication -- Fiction; Schools -- Fiction; Arithmetic -- Fiction; Dreams -- Fiction; Multiplication -- Fiction; School stories